Factors influencing mobile shoppers’ satisfaction and repurchase intention in mobile shopping in Malaysia - Mohd Paiz, Nur Ain (2021)
The growth of mobile shopping is causing consumers to change their shopping behaviour. It is essential to understand the factors of repurchase intention on the mobile shopping context. However, there are some issues arise such as bad reviews on the quality of mobile website or app service, high risk and cost, and frauds in mobile shopping may affect mobile shoppers’ behaviour. Therefore, the aim of this research is to investigate the factors that influence the mobile shoppers’ satisfaction and repurchase intention of mobile shopping in Malaysia with the support of Social Cognitive Theory (SCT) and Service Evaluation Model (SE). More specifically, this research examines the relationships between factors namely sacrifice (SAC), service quality (SQ), perceived value (PV), and trust (TR) mediated by mobile shoppers’ satisfaction (CS) with repurchase intention (RI) on mobile shopping. A total of 460 questionnaires for this research were distributed at shopping malls located in Kuala Lumpur and Selangor. The data were analysed using SPSS and Structural Equation Modelling in PLS. The research results showed that there are significant relationships between SQ and PV. Meanwhile, SAC is not significant related to PV. SAC, SQ, PV, and TR have significant positive influence on CS. CS has a significant relationship with RI. Besides, CS mediates the relationship between SAC, SQ, PV and TR. The study implies that practitioners should understand and focus on the factors of SAC, SQ, PV and TR which influence CS and RI by mediating effect of CS, to retain the customers and get more customers by encouraging use of mobile shopping. The findings contribute valuable theoretical and managerial implications that can enhance mobile shopping services.